2017
DOI: 10.4172/2157-7013.1000278
|View full text |Cite
|
Sign up to set email alerts
|

Biologically Synthesized Gold Nanoparticles using Ocimum sanctum (Tulsi Leaf Extract) Induced Anti-Tumor Response in a T Cell Daltons Lymphoma

Abstract: The characterizations of green synthesized gold nanoparticles (AuNPs) prepared using Ocimum sanctum leaf extract were done by UV-Spectrophotometer at 500-540 nm. The XRD data obtained were found similar to gold JCPDS File No-04-0784. SEM and TEM analysis of AuNPs revealed spherical shape and size of 12-20 nm. Further FT-IR data indicated the various biomolecules present in Ocimum sanctum leaf extract provides stability to gold nanoparticles synthesis. The AuNPs were studied for their anti-cancer activity on Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Oxidative Medicine and Cellular Longevity [32]. In this study, the least toxicity of Au@CDs was observed which might be due to the CD shell over the gold particles that renders them nontoxic.…”
Section: Assessment Of In Vitro Toxicity Of Synthesizedmentioning
confidence: 52%
See 1 more Smart Citation
“…Oxidative Medicine and Cellular Longevity [32]. In this study, the least toxicity of Au@CDs was observed which might be due to the CD shell over the gold particles that renders them nontoxic.…”
Section: Assessment Of In Vitro Toxicity Of Synthesizedmentioning
confidence: 52%
“…In the present case, the highest inactivation of cell proliferation was observed in Ag@CDs, which can be attributed to the Ag + ions that form the integral core of the particles. In a similar instance, gold NPs have been reported to inhibit the proliferation of dalton lymphoma cells, with around 40-50% viability at a concentration range of 80–100 μ g [ 32 ]. In this study, the least toxicity of Au@CDs was observed which might be due to the CD shell over the gold particles that renders them nontoxic.…”
Section: Resultsmentioning
confidence: 99%
“…These peaks are indexed as the cubic structure of AuNPs with space group Fm3m (225) and matched with JCPDS file no. 04-0784 (Gautam et al, 2017).…”
Section: Structural and Microscopic Analysismentioning
confidence: 99%
“…Furthermore, the same treatment significantly increased the expression of caspase-3 and -9 after 24 h. These findings indicated that the mitochondrial intrinsic pathway was activated to produce the apoptogenic responses [178]. Using an MTT assay, Gautam et al (2017) reported that b-AuNPs prepared from Ocimum sanctum leaf extract displayed cytotoxicity toward Dalton's lymphoma (DL) cells. b-AuNPs decreased mitochondrial-membrane potential (∆Ψm) and, thereby, induced apoptosis through the mitochondrial pathway.…”
Section: Induction Of Apoptosismentioning
confidence: 96%